Analisis Kinerja Pegawai Dalam Meningkatkan Kualitas Pelayanan Publik Di Kantor Camat Habinsaran Kabupaten Toba - Pane, Debora; Batubara, Beby Masitho; Angelia, Nina (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This study aims to evaluate the performance of Habinsaran Sub-District Employees in improving the quality of public services. The method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. Data is obtained from official documents and archives. The indicators used refer to the theory of Productivity, Responsiveness, and Accountability by Lohman Mahsun. The results showed that the performance of Habinsaran sub-district employees had been carried out quickly and precisely and was responsive to the aspirations of the community. Supporting factors include cooperation with village officials, communication with Social Services, and WhatsApp groups. However, obstacles such as large village distances, weak cellphone signals, and poor road quality affect performance. One of the problems found is the lack of employee time discipline, such as leaving before work hours are over and leaving the room during working hours.